2022
DOI: 10.3390/pharmaceutics14071444
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Delivery of the Protein Kinase C-β Inhibitor Ruboxistaurin Using Non-Invasive Nanoparticles of Polyamidoamine Dendrimers

Abstract: Ruboxistaurin (RBX) is an anti-vascular endothelial growth factor (anti-VEGF) agent that is used in the treatment of diabetic retinopathy and is mainly given intravitreally. To provide a safe and effective method for RBX administration, this study was designed to develop RBX nanoparticles using polyamidoamine (PAMAM) dendrimer generation 5 for the treatment of diabetic retinopathy. Drug loading efficiency, and in vitro release of proposed complexes of RBX: PAMAM dendrimers were determined and the complexation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 50 publications
3
14
0
Order By: Relevance
“…Nanotechnology has been used in medicine more and more over the past few decades, including applications for safer and more efficient tumor targeting, detection, and treatment [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. Drug delivery methods based on nanoparticles (NPs) have demonstrated a number of benefits in the treatment of cancer, including good pharmacokinetics, accurate targeting of tumor cells, a decrease in adverse effects, and reduced drug resistance [ 21 , 22 , 23 , 24 , 25 ]. Nevertheless, nanomedicine-based formulations have some demerits, such as difficulty in physical handling due to smaller size, particle aggregation, limited drug loading, and burst release [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nanotechnology has been used in medicine more and more over the past few decades, including applications for safer and more efficient tumor targeting, detection, and treatment [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. Drug delivery methods based on nanoparticles (NPs) have demonstrated a number of benefits in the treatment of cancer, including good pharmacokinetics, accurate targeting of tumor cells, a decrease in adverse effects, and reduced drug resistance [ 21 , 22 , 23 , 24 , 25 ]. Nevertheless, nanomedicine-based formulations have some demerits, such as difficulty in physical handling due to smaller size, particle aggregation, limited drug loading, and burst release [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, polymeric carriers are employed for delivering drugs to treat retinal diseases, such as acyclovir, superoxide dismutase, and imatinib. 11,12,95,96 PLGA, PEG, and other similar compounds have been frequently utilized as carriers for delivering drugs in the field of ophthalmic medicine. Through clinical trials, they have demonstrated the ability to sustain the release of drugs while maintaining an acceptable safety profile.…”
Section: Viral Vectorsmentioning
confidence: 99%
“…This renders them suitable for utilization in intricate physiological environments, including the posterior of the eye. , The diverse nature of polymer molecules, along with their varying hydrophobicity, renders them highly inclusive of both hydrophilic and hydrophobic drugs as well as biologically active proteins. Therefore, polymeric carriers are employed for delivering drugs to treat retinal diseases, such as acyclovir, superoxide dismutase, and imatinib. ,,, PLGA, PEG, and other similar compounds have been frequently utilized as carriers for delivering drugs in the field of ophthalmic medicine. Through clinical trials, they have demonstrated the ability to sustain the release of drugs while maintaining an acceptable safety profile. , Furthermore, noninvasive topical delivery polymer drug delivery systems are extensively employed in the treatment of retinal diseases. ,, …”
Section: Conventional Nanocarriers For Retinal Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…For the treatment of DR, it is a safe alternative to invasive intravitreal injection. The study conducted by Rehab A. et al employed polyamidoamine (PAMAM) dendrimer nanoparticles and designed a non‐invasive therapeutic approach using Ruboxistaurin (RBX) in order to optimize the treatment outcomes for diabetic retinopathy 97 . Additionally, Xin et al demonstrated that treatment with G4PAMAM/VEGF Antisense oligodeoxynucleotides (VEGFASODN) effectively hinders the proliferation of retinoblastoma (SO‐RB50) cells.…”
Section: Nanoparticulate Drug Deliverymentioning
confidence: 99%